Investigating Main Character’s Perfectionism in the Black Swan Movie (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
This research aims to explore the connection between socially prescribed perfectionism and conflict, particularly how perfectionism can trigger various conflicts. Focusing on Nina Sayers, the protagonist of the film Black Swan, the study examines how her perfectionism contributes to both internal and external conflicts. The motivation for this research stems from a notable lack of studies linking socially determined perfectionism to conflict, particularly its role in eliciting psychological distress and interpersonal tensions. Using the Black Swan movie as a data source, observations and note-taking techniques were employed to identify key scenes illustrating Nina's struggles. The study employs qualitative methods and descriptive techniques, presenting its findings informally. It draws on the Multidimensional Perfectionism theory by Hewitt et al. and Kenney's conflict theory. Findings reveal that Nina embodies socially prescribed perfectionism traits, including the intense desire for perfection to earn recognition and acceptance. Her interactions with influential characters, such as Thomas (the ballet director), Beth (a former star dancer), Lily (her rival), and her controlling mother, shape her perfectionist tendencies. This leads to significant internal conflict due to psychological pressure and obsession, while external conflict arises from competition and unrealistic expectations, with her need for validation exacerbating both internal and external conflicts.